Speaking emissaries: Lebanese women's rights NGO KAFA and its media use for audience mobilization. Issue 2 (1st February 2021) - Partain, Laura P. B.
Abstract: Focusing on a women's rights group in Lebanon, KAFA, this article offers a discursive reading of the NGO's campaign strategies that transform discussions of gender-based violence from a private familial to a public societal issue. KAFA, 'enough' in Arabic, engages its audience on mediated platforms, providing audiences with participatory strategies through images and videos. I ground my analysis in my interview with KAFA's communication director, interrogating KAFA's innovative media strategies to build a wider movement. Using global media and performance theory, I examine how pedagogical media strategies expand the public sphere and facilitate audience intervention into systemic issues. These media strategies act as necessary scaffolds towards building nation-wide support against gender-based violence.